2017
DOI: 10.1177/0363546517707202
|View full text |Cite
|
Sign up to set email alerts
|

A Long Preoperative Duration of Symptoms Is Associated With Worse Functional Outcomes After 1-Stage Arthroscopic Treatment of Rotator Cuff Tears With Shoulder Stiffness

Abstract: One-stage surgery effectively achieved overall improvements. A preoperative DOS of ≥6 months led to poorer functional outcomes, which suggests that surgeons should propose a surgical treatment for this condition before symptoms persist for 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Patients with rotator cuff tears with shoulder stiffness had limited motion of shoulder joints, like significant reductions in functional score of Constant and Murley together with SROM. Our analysis was in agreement with other groups’ investigations showing that patients inflicted with this disorder, independent of the gender, BMI, and involved side, underperformed in shoulder function [35,36,37]. While the cause of shoulder stiffness remains unclear, increasing evidence reveals that defective subacromial bursa integrity is associated with the shoulder disorder.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with rotator cuff tears with shoulder stiffness had limited motion of shoulder joints, like significant reductions in functional score of Constant and Murley together with SROM. Our analysis was in agreement with other groups’ investigations showing that patients inflicted with this disorder, independent of the gender, BMI, and involved side, underperformed in shoulder function [35,36,37]. While the cause of shoulder stiffness remains unclear, increasing evidence reveals that defective subacromial bursa integrity is associated with the shoulder disorder.…”
Section: Discussionsupporting
confidence: 92%
“…This is in contrast to patients with rotator cuff tears and frozen shoulder managed arthroscopically where a longer duration of symptoms is associated with a poorer outcome. 20 The benefits of arthroscopic capsular release for our patients are the avoidance of fractures and other intraarticular injuries that can occur with manipulation under anaesthesia. 21 We did not have any recurrence of frozen shoulder in our series of patients.…”
Section: Discussionmentioning
confidence: 99%
“…32 These differences between the groups were significant both at 6 months ( P = .047) and at 2 years ( P = .009). 32 Furthermore, previous studies have reported retear rates of 6.1%, 37 12.1% or 13.3%, 26 and 13.4% 2 in patients with RCTs and shoulder stiffness. These rates were not compared with those in patients with RCTs only.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, a preoperative duration of symptoms of ≥6 months was reported to be associated with worse functional outcomes after 1-stage surgery for RCTs with shoulder stiffness, and surgical treatment for this condition within 6 months of symptom onset was suggested. 2 Therefore, 1-stage arthroscopic treatment of RCTs concomitant with shoulder stiffness can save time and help patients avoid unnecessary rehabilitation. 26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation